PENGEMBANGAN MEDIA “RUMPUT KEKAL” BERBASIS LITERASI BUDAYA DALAM MENINGKATKAN MOTIVASI BELAJAR IPAS SISWA - Dian Puspita Sari; Mardi Widodo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was conducted with the aim of developing learning media. “RUMPUT KEKAL” (Local Wisdom Rotating House) based on cultural literacy in order to improve the learning motivation of grade III Elementary School students. The process of developing this media includes validation by media experts, language experts, and material experts. The validation results show that the developed media obtained a score of 73 (85.8%) from media experts, 40 (88.8%) from language experts, and 51 (92.72%) from material experts, all in the very good (valid) category. After being declared valid, this media was tested in grade III of UPT SD Negeri Karangrejo 2 with 22 students. The trial was conducted in two meetings: the first without media and the second using RUMPUT KEKAL media. The effectiveness of the media was measured through pretest and posttest evaluations, with an average N-Gain result of 0.78, which indicates a high category with a percentage of 78.3%. The final evaluation stage showed that this media was practical to use, with a score of 51 (average 4.6) from teachers and a score of 1,128 (93.22%) from students, both in the very practical category. Thus, the RUMPUT KEKAL media is expected to provide a positive contribution in increasing students' learning motivation and helping them understand and preserve local cultural heritage.